Inconstitucionalidad del Cobro del Impuesto sobre la Renta de Jubilaciones, Pensiones y Haberes de Retiro. Violación a Derechos Humanos: El Caso Mexicano - Castorena Álvarez, Guillermo (2014)
The first part of the article establishes the background and acts of authority that let the victims to file the constitutional claims. Then it enters to analyze different arguments that were made to the Mexican Courts against the acts of authority. Finally the article refers to the Human Rights that the autor considers violated. These arguments were filled to the Inter-American Commission on Human Rights.